Proteomic Characterization of Human Neural Stem Cells and Their Secretome During in vitro Differentiation - Červenka, Jakub; Tylečková, Jiřina; Kupcová Skalníková, Helena; Vodičková Kepková, Kateřina; Poliakh, Ievgeniia; Valeková, Ivona; Pfeiferová, Lucie; Kolář, Michal; Vaškovičová, Michaela; Pánková, Tereza; Vodička, Petr (Frontiers in Cellular Neuroscience, 2021)
Cell therapies represent a promising approach to slow down the progression of currently untreatable neurodegenerative diseases (e.g., Alzheimer's and Parkinson's disease or amyotrophic lateral sclerosis), as well as to support the reconstruction of functional neural circuits after spinal cord injuries. In such therapies, the grafted cells could either functionally integrate into the damaged tissue, partially replacing dead or damaged cells, modulate inflammatory reaction, reduce tissue damage and support neuronal survival by secretion of cytokines, growth, and trophic factors. Comprehensive characterization of cells and their proliferative potential, differentiation status and population purity before transplantation is crucial to prevent safety risks, e.g., a tumorous growth due to the proliferation of undifferentiated stem cells. We characterized changes in proteome and secretome of human neural stem cells (NSCs) during their spontaneous (EGF/FGF2 withdrawal) differentiation and differentiation with trophic support by BDNF/GDNF supplementation. We used LC-MS/MS in SWATH-MS mode for global cellular proteome profiling and quantified almost three thousand cellular proteins. Our analysis identified substantial proteins differences in the early stages of NSC differentiation with more than a third of all the proteins regulated (including known neuronal and NSC multipotency markers) and revealed that the BDNF/GDNF support affected more the later stages of the NSC differentiation. Among the pathways identified as activated during both spontaneous and BDNF/GDNF differentiation were HIF-1 signaling pathway, Wnt signaling pathway and VEGF signaling pathway. Our follow-up secretome analysis using Luminex multiplex immunoassay revealed significant changes in the secretion of VEGF and IL-6 during NSC differentiation. Our results further demonstrated an increased expression of Neuropilin-1 as well as Catenin β-1, both known to participate in regulation of VEGF signaling, and showed that VEGF-A isoform 121 (VEGF121), in particular, induces proliferation and supports survival of differentiating cells.